Does Trade Openness Reduce Inflation? Empirical Evidence from Ethiopia (Global Journal of Management and Business Research, 2017)
Of the most commonly celebrated propositions in international trade is the hypothesis that trade liberalization is associated with declining prices, so that protectionism is inflationary. The New Growth Theory is strongly in favor of this view. However, the "Cost-push advocators" claim for the existence of positive correlations between trade openness and inflation variables. Moreover, empirical studies have been confirming inconclusive results regarding the nature of relationships between the two variables. These theoretical and empirical departures are the principal motivations to the current study. This study is aimed to test the relationship between inflation and trade openness variables in Ethiopia, using the time series data set for the period serially ranging from 1976/77 to 2016/77. Augmented Dickey Fuller and Phillips Perron approaches will be employed for testing the stationarity properties of individual variables in the model and the Johnson's maximum likely-hood approach will be employed for cointegration tests.
Keywords: cointegration; ethiopia; inflation; openness; vector error correction model 1